Sugar Policy and Reform - Larson, Donald F. (World Bank, Washington, DC, 2014)
Reviewing cross-country experience with sugar policies, and policy reform, the authors conclude that long-standing government interventions - rooted in historical trade arrangements, fear of shortages, and conflicting interests between growers, and sugar mills - often displace both the markets, and the institutions required to produce efficient outcomes. Arrangements rooted in colonial eras, still shape policies, and trade in the United States, the European Union (EU), and many developing countries. Once policies, and institutions are put in place, households, and the value of investments grow dependent on them, even as their usefulness fades. Firms and households make decisions that are costly to reverse. And the result is a legacy of path-dependent policies, in which approaches, and instruments are greatly influenced by past agreements, and previous interventions. The cumulative effects of these interventions are embodied in livelihoods, political institutions, capital stocks, and factor markets - which not only dictate the starting point for reform, but also determine which reform paths are feasible. Experiments with public ownership, common in many countries, have not succeeded. So most countries have initiated some measure of market reform. And events relating to NAFTA, Lome, and expansion of the EU, may bring about significant changes in the EU, and US sugar regimes, with cascading effects on other countries. Common problems in the sector include determining cane quality, finding methods for fairly sharing revenues from joint production, finding ways to take advantage of preferential trade arrangements with minimal negative consequences, finding ways to finance, and encourage research, and other activities with common benefits, identifying practices that facilitate equitable, sustainable privatization, and determining the relationship between sugar market reform, and markets in land, water, credit, and other inputs.